The specialized language of grammar in L2 Italian textbooks: terminology and implications for language pedagogy - Nitti, Paolo (Kwartalnik Neofilologiczny, 2026)
This study analyzes how grammar is presented in twenty-five Italian L2/LS textbooks published since 2019, focusing on grammatical terminology, rule presentation, and consistency of specialist vocabulary. Particular attention is given to the role of these elements in fostering learners’ metalinguistic awareness, one of the key factors in second-language acquisition, enabling learners to monitor linguistic structures and refine learning strategies. The analysis highlights significant heterogeneity in terminology use in textbooks, reflecting differing editorial and methodological approaches that may affect learners’ understanding. It was structured around three dimensions: the range of grammatical terminology, the clarity of definitions, and the organization of grammatical content.